Implementasi Metode Market Basket Analysis Pada Sistem Penjualan Dan Pemasaran Pada Butik Nazwa Fashion - Tika Wati; Vivi Sahvitri; Kiky Rizky Nova Wardani (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
Nazwa Fashion Boutique Shop is a shop that sells various kinds of women's fashion such as clothes, pants, skirts and hijab clothing with various brands and prices. The Nazwa Fashion Boutique Shop is located at Jalan D.I Panjaiatan No.1 Kelurahan 16 ULU Kec. SU2 RT.32 RW.10 which has been established since 2013 or less than 5 years. During the sales process at the Nazwa Boutique Shop Mode is still done manually, ie prospective buyers come directly at the Nazwa Mode Boutique Shop to buy products Clothing available on the storefront store. This is less effective because consumers incur considerable costs. To overcome this problem, the author tries to provide a solution to build media sales transactions online, the online sales transaction media is to build an E-Commerce website using the Basket Market Analysis method as one of the media for sales and promotions that is useful to help companies market the products it sells and is targeted to manage again get income and increase the stock of goods in the warehouse. In addition, the existence of online transactions can make it easier for consumers to choose and order products they want so they can increase company profits.